2013
DOI: 10.4209/aaqr.2012.11.0329
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol-Cloud-Interaction Variability Induced by Atmospheric Brown Clouds during the 2009 Indian Summer Monsoon Drought

Abstract: Contrasting monsoons of 2008 and 2009 provided a test bed to enhance the understanding of the aerosol variability and aerosol-cloud interaction. Vertical aerosol profiles derived from the Cloud-Aerosol Lidar and Infrared Pathfinder Satellite Observations (CALIPSO) are used to delineate the aerosol properties during the two contrasting Indian summer monsoons. We observed a 30-40% increase in the aerosol occurrence frequency (AOF) in lower altitudes (below 6 km) in 2009 and a 5-8% enhancement in AOF at higher al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 32 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…Wild and Roeckner [] found systematically underestimated atmospheric shortwave absorption along with overestimated surface shortwave absorption at low latitudes in ECHAM5 and related these errors to the crude aerosol climatology used in the physical parameterization package, which does not take into account high regional and seasonal loadings of absorbing aerosols. During the past few decades, direct surface radiation measurements observed continuous and steady dimming in India associated with tremendous aerosol emissions due to rapid urbanization and population growth [ Wild et al , ], and more recent studies with satellite observations noticed increased aerosol loadings over central India especially during break conditions [e.g., Manoj et al , ; Bhawar and Rahul , ]. Since the ECHAM5 aerosol climatology is also implemented in HIRHAM5, we assume that anomalous high‐simulated incoming surface shortwave radiation flux during breaks is perhaps partly due to weak atmospheric aerosol absorption.…”
Section: Hirham5 Mse Budgetmentioning
confidence: 99%
“…Wild and Roeckner [] found systematically underestimated atmospheric shortwave absorption along with overestimated surface shortwave absorption at low latitudes in ECHAM5 and related these errors to the crude aerosol climatology used in the physical parameterization package, which does not take into account high regional and seasonal loadings of absorbing aerosols. During the past few decades, direct surface radiation measurements observed continuous and steady dimming in India associated with tremendous aerosol emissions due to rapid urbanization and population growth [ Wild et al , ], and more recent studies with satellite observations noticed increased aerosol loadings over central India especially during break conditions [e.g., Manoj et al , ; Bhawar and Rahul , ]. Since the ECHAM5 aerosol climatology is also implemented in HIRHAM5, we assume that anomalous high‐simulated incoming surface shortwave radiation flux during breaks is perhaps partly due to weak atmospheric aerosol absorption.…”
Section: Hirham5 Mse Budgetmentioning
confidence: 99%
“…The atmospheric radiative heating due to BC increases the atmospheric stability leading to a change in the precipitation patterns282930 and when such heating occurs over glaciers/ice, it enhances the melting rate as proved in a recent study31. Several studies about the aerosol variability and the associated heating have been conducted over the Himalayan region3233343536 and BC induced heating rates greater than 2 K/day have been reported over different Indian regions1637.…”
Section: Discussionmentioning
confidence: 93%
“…An increase in anthropogenic activity has led to an increase in aerosol emissions at a global scale, which led to an increase in cloud condensation nuclei (CCN) and ice nucleating particles (INP) (Seinfeld et al, 2016). However, the increase in CCN does not lead to enhanced precipitation, indicating complex microphysical processes affecting the precipitation (Koren et al, 2008;Bhawar and Rahul, 2013). Previous studies reported an adverse effect of aerosol increase and thereby giant CCN formation on precipitation (Posselt and Lohmann 2008).…”
Section: Introductionmentioning
confidence: 99%